A review of the populations of tilapiine species in lakes Victoria and Naivasha, East Africa. Issue 3 (3rd July 2021) - Yongo, Edwine; Cishahayo, Laurent; Mutethya, Eunice; Alkamoi, Bonface Mnang'at; Costa, Kokwon; Bosco, Nzeyimana Jean
Abstract : This paper discusses the catch trends, population attributes and biological characteristics of tilapiine species that are both native and that have been introduced into Lake Victoria and Lake Naivasha. Predation by Lates niloticus, species hybridisation, overfishing, pollution and eutrophication have negatively impacted endemic fish stocks in these lakes. Four tilapiine species, Oreochromis niloticus, Oreochromis leucostictus, Coptodon zillii and Coptodon rendalli, and three tilapiine species, O. niloticus, C. zillii and O. esculentus, were hence introduced into Lake Victoria and Lake Naivasha, respectively, to improve fish catches following collapse of native fish stocks. Establishment of these non-native species was associated with declines in populations of the native Oreochromis esculentus and Oreochromis variabilis, and O. niloticus now dominates commercial tilapiine fishery in Lake Victoria. The fishery catches in Lake Naivasha were dominated by the introduced O. leucostictus and O. niloticus, whereas C. zillii is rarely caught. The biological and population attributes of the tilapiines in both lakes have shown great variations over time. There is, therefore, a need for implementation of effective management measures, including control of fishing effort, pollution control and protection of surrounding wetlands, to promote recovery and long-term sustainability of the fishery resources of these lakes.